Deterioration of the Global Arms Control Regime and the Role of the Vienna Document in Reviving Stability and Confidence in Europe - Stefanović, Andrej (Journal of Regional Security, 2021)
The author explores the deterioration and (forthcoming) collapse of the global arms control system, with special consideration given to potential consequences this event would have for the European continent. In this context, and in assessing the significance of the remaining mechanisms for preventing a potential arms race and deepening of conflict in Europe, he draws attention to the OSCE Vienna Document, as a tool which could enable the revival of stability through confidence building in Europe, especially in view of its capacity for adaptation and modernization.
Keywords: arms control; Vienna Document; OSCE; Europe; confidence building